IMPLEMENTASI STASIUN BUMI TT AND C SATELIT LAPAN-TUBSAT DI BIAK - Judianto, Chusnul Tri (Indonesian Journal of Aerospace, 2007)
LAPAN-TUBSAT as a satellite pioner project established by LAPAN finally successfully launched on 10 January 2007. The usage of the main payload of the satellite especially can be used for capturing the surface of the globe. All data are captured by the camera in the video analog format and will be transmitted through s-band frequency in FM video modulation. For controlling the attitude and monitoring the health of the satellite, all data telemetry will be transmitted to the ground station on UHF frequency (437,325 MHz). The space craft control center for LAPAN-TUBSAT satellite has been established in Rumpin Bogor. This station will cover from west part until centre part of Indonesia's archipelago. Rumpin ground station situated on 6.22 Deg South and 106.37 Deg East. For covering entire part of Indonesia, its planed to establish a new ground station in Biak Island PApua at 1.17 Deg South and 136.1 Deg East. Design until implementation of this ground station will be elaborated deeply in this paper. Keywords: LAPAN-TUBSAT, TT and C Ground station.